The type and quantity of dietary fat and carbohydrate alter faecal microbiome and short-chain fatty acid excretion in a metabolic syndrome ‘at-risk’ population - Fava, F; Gitau, R; Griffin, B A; Gibson, G R; Tuohy, K M; Lovegrove, J A (International Journal of Obesity, 2013)
INTRODUCTION AND OBJECTIVES: An obese-type human microbiota with an increased Firmicutes:Bacteroidetes ratio has been described that may link the gut microbiome with obesity and metabolic syndrome (MetS) development. Dietary fat and carbohydrate are modifiable risk factors that may impact on MetS by altering the human microbiome composition. We determined the effect of the amount and type of dietary fat and carbohydrate on faecal bacteria and short chain fatty acid (SCFA) concentrations in people ‘at risk’ of MetS. DESIGN: A total of 88 subjects at increased MetS risk were fed a high saturated fat diet (HS) for 4 weeks (baseline), then randomised onto one of the five experimental diets for 24 weeks: HS; high monounsaturated fat (MUFA)/high glycemic index (GI) (HM/HGI); high MUFA/low GI (HM/LGI); high carbohydrate (CHO)/high GI (HC/HGI); and high CHO/low GI (HC/LGI). Dietary intakes, MetS biomarkers, faecal bacteriology and SCFA concentrations were monitored. RESULTS: High MUFA diets did not affect individual bacterial population numbers but reduced total bacteria and plasma total and LDL-cholesterol. The low fat, HC diets increased faecal Bifidobacterium ( P =0.005, for HC/HGI; P =0.052, for HC/LGI) and reduced fasting glucose and cholesterol compared to baseline. HC/HGI also increased faecal Bacteroides ( P =0.038), whereas HC/LGI and HS increased Faecalibacterium prausnitzii ( P =0.022 for HC/HGI and P =0.018, for HS). Importantly, changes in faecal Bacteroides numbers correlated inversely with body weight ( r =−0.64). A total bacteria reduction was observed for high fat diets HM/HGI and HM/LGI ( P =0.023 and P =0.005, respectively) and HS increased faecal SCFA concentrations ( P <0.01). CONCLUSION: This study provides new evidence from a large-scale dietary intervention study that HC diets, irrespective of GI, can modulate human faecal saccharolytic bacteria, including bacteroides and bifidobacteria. Conversely, high fat diets reduced bacterial numbers, and in the HS diet, increased excretion of SCFA, which may suggest a compensatory mechanism to eliminate excess dietary energy.